Co-Movement of COVID-19 Deaths, Stock Returns and Oil Prices in the BRICS: Wavelet Coherence and Partial Wavelet Analysis (Journal of Asian Development Studies, 2025)
This study analyses the relationship between COVID-19 deaths, stock returns, and crude oil price volatility shock in the BRICS using wavelet power spectrum, wavelet coherency, and partial wavelet coherency (PWC). First, using weekly data from January-March 2020 to October 2022, we examine the wavelet power spectrum of stock returns for each country. Second, we analyse the co-movement between coronavirus deaths and stock returns in the short, medium, and long term. Third, we identify the connectedness between coronavirus deaths and stock returns after removing the effect of crude oil prices. The findings reveal that the stock returns of all countries exhibited high fluctuation during COVID-19 at first but China’s stock returns showed dramatic volatility over the entire sample period. Considering wavelet coherency, the strong connectedness at low, middle, and high frequencies shows that COVID 19 had a positive effect on stock returns for Brazil, Russia, India, and South Africa and the stock returns lead. For China, stock returns led until June 2020, and then COVID-19 led. For PWC, the considerable area decrease shows that crude oil price is a key driver of the co movement between COVID-19 deaths and stock returns for Brazil, Russia, and India compared to benchmark (wavelet coherency) results. For China and South Africa, the PWC area increased considerably but the interdependence between series is stronger in China than in South Africa. This means that the crude oil price may not be an essential determinant of the interdependence between COVID-19 and stock returns in China and South Africa.